The Effect of Clay Therapy on The Quality of Life of Pediatric Oncology Patients - Kürtüncü, Meltem; Utaş Akhan, Latife; Yıldız, Hicran; Demirbağ, Birsel Canan; Kurt, Aylin (Caring: Indonesian Journal of Nursing Science, 2023)
Some interventions in pediatric oncology care for pediatric patients, such as art therapy and play therapy, ensure the physical and emotional well-being of patients. It also has the potential to improve quality of life during treatment and at the end of life. We aimed to determine the effect of clay therapy on the quality of life of pediatric oncology patients. This study was conducted with nine children (intervention group/clay therapy) inpatients in haematology units and nine children (comparison group). The “KINDL Quality of Life Scale” was used. The children participated for eight weeks in clay applications for two days a week. The post-test (69.66±15.70) of the KINDL Quality of Life Scale total mean score of the children in the intervention group was higher than the pre-test (57.00±10.54) (Z = 2.670; p = 0.008). There were no significant differences between the pre-test (74.66±5.97) and the post-test (74.55±6.94) of the quality of life of the children in the comparison group (Z = 0.005; p = 0.755). Clay therapy should be included in nursing care interventions to increase the quality of life for pediatric oncology patients. To increase quality of life, especially in pediatric oncology patients, it is suggested that environments be formed in hospitals where clay therapy can be applied. .